A Taxonomy and Capacity Planning Technique for Sustainable Cloud Computing – An Extensive Overview - Eswaran, Sivaraman (Journal of Ubiquitous Computing and Communication Technologies, 2022)
This overview of study intends to provide a thorough taxonomy of sustainable cloud computing capacity planning strategies. Several academic and industrial organizations have suggested several approaches to sustainability, and this taxonomy is used to analyze them. These modern methods have been analyzed and grouped together according to their shared traits and characteristics. This study takes a holistic look at sustainable Cloud Data Centers (CDCs), surveying the supporting methods and technologies along the way. It provides examples of successful capacity planning in sustainable CDCs based on research and practice from academia and industry. Moreover, the paper presents the most recent findings on what it takes to make CDCs viable. In addition, the difficulties of integration and the unanswered questions of sustainable CDC research have been discussed.